PERAN LEMBAGA KEUANGAN SYARIAH PENERIMA WAKAF UANG (LKS-PWU) BAGI OPTIMALISASI WAKAF UANG - Hastuti, Qurratul ‘Aini Wara (ZISWAF, 2017)
Sharia Financial Institutions Receiving money Waqf (LKS-PWU) has a very important role for the optimization of money waqf. This is because the money waqf can not be submitted directly to nazhir, but must go through the Sharia Financial Institution Receiver of Money Waqf (LKS-PWU). And to support it, the Sharia Financial Institution Receiving Money Waqf should have professional management in the collection, as well as management mechanisms, and need accountability and integrity in the reporting side of the management of waqf money received.